Determining the effectiveness of oar blades in rowing - Kleshnev, V. V.; Andreeva, E. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the main theoretical principles and measurement methods and provide practical examples of how to correctly determine the efficiency of a rowing blade in academic rowing.